DEVELOPMENT OF INFORMATION RESOURSE FOR MINERAL WATER DEPOSITS KMV - K. V. Martirosyan; A. V. Martirosyan; A. A. Makarova; A. S. Zyuzin (Современная наука и инновации)
The article deals with development methods of information resourses for mineral water deposits. It provides practical example design of company information resourse, that destined for mineral water deposits information promotion. This work determine structured thematic content methods. The proposed structure of the information resourse provides an effective commercialization.